2014
DOI: 10.4271/2014-01-9049
|View full text |Cite|
|
Sign up to set email alerts
|

Parameter Estimation of a DOC from Engine Rig Experiments with a Discretized Catalyst Washcoat Model

Abstract: Parameter tuning was performed against data from a full scale engine rig with a Diesel Oxidation Catalysts (DOC). Several different catalyst configurations were used with varying Pt loading, washcoat thickness and volume. To illustrate the interplay between kinetics and mass transport, engine operating points were chosen with a wide variation in variables (inlet conditions) and both transient and stationary operation was used. A catalyst model was developed where the catalyst washcoat was discretized as tanks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…A thorough description of the experimental set-up, measurements and engine operation design is given in the preceding study (Lundberg et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A thorough description of the experimental set-up, measurements and engine operation design is given in the preceding study (Lundberg et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The heat transfer parameters including thermal mass (s heat ), environmental temperature (T ∞ ), and a lumped heat transfer coefficient (˛t ot ) were earlier tuned to a satisfactory fit in (Lundberg et al, 2014) for the system at hand and will therefore not be retuned in the current study.…”
Section: Adjustable Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…With a full DOC feed mixture, a number of global kinetic models are present in the literature based on the common Voltz model [13] obtained from lab tests [14,15] to the full-scale engine rig test [16]. Recently, Khosravi et al [14,15] reported a global kinetic model for the NO oxidation reaction in the presence of C3H6 over Pt and bimetallic Pt:Pd catalysts which includes C3H6-SCR, NO oxidation, C3H6 oxidation and N2O formation.…”
Section: Introductionmentioning
confidence: 99%